Analytical performance of a low‐cost multiplex polymerase chain reaction human papillomavirus genotyping assay for use in Sub‐Saharan Africa - Samwel, Kandali (J Med Virol, 2018)
We have tested a multiplex polymerase chain reaction (PCR) human papillomavirus (HPV) genotyping assay to fill the need for rapid and low‐cost HPV detection in Sub‐Saharan Africa. This method allows high throughput genotyping and simultaneous detection of 14 high‐risk and two low‐risk HPV types, by PCR amplification of HPV DNAs in a single reaction tube. In this study, we describe stepwise experiments to validate the multiplex HPV PCR assay for determination of HPV genotypes from 104 cervical brush samples from Tanzanian women. Assay performance was evaluated by determination of intra‐laboratory reproducibility, sensitivity, and specificity. Further performance was assessed by comparison with the widely accepted and validated HPV My09/My11 amplification and hybridization assay. Statistics; the Cohen kappa (κ) and McNemar P values were used to analyze interobserver and intermethod agreement. Overall concordance between the multiplex and line blot hybridization assays was 99% (per sample) with a κ value equal to 0.95; and 96.49% (per detection event) with a κ value of 0.92. Interobserver reproducibility of the assay per sample was 95.76% with κ of 0.91. These results demonstrate that the multiplex HPV PCR assay has high analytical sensitivity and specificity in detecting as many as 16 different HPV genotypes and that its simplicity and low cost makes it well suited for sub‐Saharan Africa.